(untitled) - Bannock, G. (Harmondsworth, 1978)
Whether readers are students of economics or simply want to follow the economic discussions in the media today, this wide-ranging and accessible dictionary is the perfect source for explanations of a host of economic terms. With a world- wide focus that befits our truly global age, the seventh edition covers recent developments in economic theory and practice and contains detailed information on economic terms and the history of economics, as well as biographies of influential economists. Addressing finance and game theory, international monetary and welfare economics, applied economics, and major financial institutions, this dictionary is truly a valuable asset for anyone interested in understanding the economic engine that makes our world turn.
Keywords: Economics,Kinh tế học